PENGARUH PELAKSANAAN PELATIHAN DAN PENGAWASAN KERJA TERHADAP KINERJA KARYAWAN PT. GREEN PLANET INDONESIA CABANG PEKANBARU - Ramadhan, Gilang; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the implementation of training and work supervision on employee performance partially and simultaneously. This study uses a questionnaire as a data collection tool which is distributed to 55 respondents to employees of PT. Green Planet Indonesia Pekanbaru branch. Data were then processed using descriptive analysis and statistical analysis using SPSS 25 to test the validity, reliability test, simple linear regression, multiple linear regression analysis, analysis of determination (R2) and hypothesis testing with test t (partial) and F test ( simultaneous). The results showed that testing the first hypothesis, namely the implementation of training on performance, namely t count (6.221)> t table (2.005), meaning that the implementation of training had a significant effect on employee performance. Second, work supervision is t count (6.289)> t table (2.005), meaning that job supervision has a significant effect on employee performance. The results of the F test (23.064)> F table (3.18) means that the implementation of training and work supervision simultaneously has a significant effect on employee performance.Keywords: Implementation of Training, Supervision of Work, Employee Performance.